Identification of flow classes in the wake of a simplified truck model depending on the underbody velocity. Issue 175 (April 2018) - Castelain, Thomas; Michard, Marc; Szmigiel, Mathieu; Chacaton, Damien; Juvé, Daniel
Abstract: An experimental study of the near wake of a simplified truck model with an aspect ratio between the height and the width greater than one is presented. The influence of the underbody velocity at a constant ground clearance height is considered. The evolution of the model base pressure and of the near wake as a function of the underbody velocity permits to identify four classes of flow. For large values of underbody velocity, typically above 60% of the free stream velocity, the near-wake structure is similar to what obtained in bluff-body characterizations where the underbody flow momentum is sufficient to prevent its detachment from the ground. For smaller values of underbody velocity, of particular interest when considering real truck applications, base pressure mean value and near wake characteristics strongly depend on the underbody velocity; three different classes are defined through the values of time-averaged rear pressure as well as a qualitative analysis of the near-wake structure. Quantitatively, a momentum budget in the near-wake together with the characterization of the curvature of the underbody flow near the model end provide ad-hoc indicators for discriminating between the different flow classes. Highlights: Base pressure changes with underbody flux of a square-back model are studied. Four different flow classes are identified at constant ground clearance. Integral parameters from flow measurements allow to distinguish the four flow classes.